2012
DOI: 10.2136/sssaj2011.0320
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Tillage Impacts on Soil Aggregation and Carbon Pools in a Sandy Clay Loam Soil of the Indian Himalayas

Abstract: All rights reserved. No part of this periodical may be reproduced or transmitted in any form or by any means, electronic or mechanical, including photocopying, recording, or any information storage and retrieval system, without permission in writing from the publisher. Permission for printing and for reprinting the material contained herein has been obtained by the publisher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
58
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(70 citation statements)
references
References 46 publications
(61 reference statements)
11
58
0
1
Order By: Relevance
“…The finding of present study is in line with the published literature on depthwise distribution of SOC in crop lands (Mandal et al, 2013;Singh et al, 2015). This study corroborated the findings of Bhattacharyya et al, (2012) suggesting thereby the advantage of minimum soil disturbance (PB and ZT) and crop wise residue retention on soil surface.…”
Section: Dehydrogenase Activitysupporting
confidence: 92%
“…The finding of present study is in line with the published literature on depthwise distribution of SOC in crop lands (Mandal et al, 2013;Singh et al, 2015). This study corroborated the findings of Bhattacharyya et al, (2012) suggesting thereby the advantage of minimum soil disturbance (PB and ZT) and crop wise residue retention on soil surface.…”
Section: Dehydrogenase Activitysupporting
confidence: 92%
“…In the current investigation, SOC data revealed that tillage practices were significant difference similar result was found Bhattacharyya et al, 2012. Cropping system and interaction between tillage and cropping system did nothave showed any significant effect on SOC content.…”
Section: Soil Organic Carbon Concentration (Soc)supporting
confidence: 79%
“…Among the cropping systems compared, soybean + P. pea S + PP and M -G was recorded significantly higher OC concentration across the tillage in 0-5 cm depth, Das et al, 2013 found that cotton based cropping system had the highest root biomass addition in soil followed by maize based cropping systems. (Bhattacharyya et al, 2012) reported that in the Indian Himalayas, a reduction in tillage intensity led to a significantly larger SOC accumulation in the surface soil layer (0-5 cm), but not in the 5-to 15-cm soil layer after 6 yr of cropping. The data show almost similar trend was observed under in 5-15 cm depth.…”
Section: Soil Organic Carbon Concentration (Soc)mentioning
confidence: 99%
“…A higher Leaf Area Index (LAI) in the soil conservation practices than in the CT plots could be due to the compounded effects of many factors, such as an additional nutrient supply, decreased competition for resources due to a lower weed density, improved soil physical properties and water regimes, better radiation interception, water extraction, aeration and less evaporation in the soil conservation practices compared with the CT plots (Unger et al, 1998;Bhattacharya et al, 2012Bhattacharya et al, , 2013Das et al, 2014). Soil structure affects crop yield through a complex of root-based mechanisms, that in turn affect above-ground biomass (Passioura, 2002).…”
Section: à2mentioning
confidence: 99%